Kondisi Potensi Wisata di Ekowisata Sungai Mudal Kabupaten Kulon Progo - Irsyad, Muhammad (Politeknik Pariwisata NHI Bandung, 2020)
This article basically has three objectives, knowing the tourism potential on Mudal River Ecotourism, knowing the stages and factors that influence tourism development and recommending tourism development efforts. To achieve these objectives the method used is descriptive qualitative by analyzing the data using weighting and scoring. The results of the study indicate that the existing tourism potential is amenity, accessibility, attractions and institutional support. The four potentials are in the 3rd phase including consolidation. The development effort that can be taken is to maximize land use without damaging the environment by taking into account the number of tourists; organize public transportation; planning management in the future; expand market segmentation and product diversification; improve the quality of human resources; actively involve local communities, align policy with the community and control the environment.